2018
DOI: 10.1007/s13178-018-0349-6
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Landscape of Support and Safety Among Sexual Minority Women and Gender Non-conforming Individuals: Perceptions After the 2016 US Presidential Election

Abstract: As part of a larger online survey, we conducted an internet-based study that included both qualitative and quantitative data from a national non-probability sample to examine how sexual minority women and gender non-conforming individuals described their experiences and concerns after the 2016 election. The current study explores responses in relation to local social and political climate. Quantitative analysis of survey responses (N=969) examined changes in participant concerns relative to state policy contex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…LGBTQ Experiences of the Election Some work has focused specifically on sexual minorities' experiences of the 2016 presidential election outcome (e.g., Brown & Keller, 2018;Drabble et al, 2019;Garrison et al, 2018;Gonzalez et al, 2018a;Lannutti, 2018;Riggle et al, 2018;Veldhuis et al, 2018). For instance, Riggle et al (2018) found that sexual minority women and gender-diverse individuals felt hopeless about the future (i.e., feelings associated with minority stress), while others described feelings of hope and empowerment.…”
Section: Racial Minority Experiences Of the Electionmentioning
confidence: 99%
“…LGBTQ Experiences of the Election Some work has focused specifically on sexual minorities' experiences of the 2016 presidential election outcome (e.g., Brown & Keller, 2018;Drabble et al, 2019;Garrison et al, 2018;Gonzalez et al, 2018a;Lannutti, 2018;Riggle et al, 2018;Veldhuis et al, 2018). For instance, Riggle et al (2018) found that sexual minority women and gender-diverse individuals felt hopeless about the future (i.e., feelings associated with minority stress), while others described feelings of hope and empowerment.…”
Section: Racial Minority Experiences Of the Electionmentioning
confidence: 99%
“…The concerns of participants echo observations from other research that access to marriage is not an adequate or equitable vehicle for providing material benefits such as health insurance (Daum, 2017) and does not provide a remedy for other forms of institutionalized discrimination (LeBlanc, Frost, & Bowen, 2018). These findings also underscore the importance of other policy events that increase stigma-related concerns, even in the context of marriage legalization (Drabble, Veldhuis, Wootton, Riggle, & Hughes, 2019; Lannutti, 2018b; Veldhuis, Drabble, Riggle, Wootton, & Hughes, 2018a, 2018b).…”
Section: Discussionmentioning
confidence: 61%
“…Rapidly rising suicide rates among millennials (Ducharme, 2019; Network, 2019), link to significant associations between minority stress and severe negative mental health (Gonzalez et al , 2018), and steadily declining self-reported emotional health of incoming college students are not a spontaneous contemporary phenomenon which exists in a vacuum. Instead, these issues present as symptoms of lived reality under late-stage capitalism (Prins et al , 2015) combined with unique stressors under the 45th presidency (Burnett-Zeigler, 2016; Drabble et al , 2018; Vega, 2018; Wray-Lake et al , 2018). Understanding the implications of neoliberalism, corporatization and post-racial ideology on students contextually (and as influenced by historical factors which contributed to the Trump presidency) is key work toward the development of minimizing harm in the classroom and developing critically informed pedagogy.…”
Section: Student Contextmentioning
confidence: 99%